An Operations management study on GE Lighting Philippines - Florendo, Michael L. (College of Engineering, 2003)
An operations management study was conducted on General Electric Lighting, Philippines. This project was concerned with solving problems in the different areas of operations in order to allow overall improvements in the company's production, finance and market performance. The study began with a comprehensive documentation on GE Lighting's corporate strategies, goals and an intensive look on the different operations management areas. These areas were product and process design, capacity planning, quality management, inventory and supply chain management, demand management, human resources and aggregate planning. In addition to documenting, meaningful insights were formed on the OM areas. Data information and insights gathered served as foundations to identifying possible problems encountered by the company. Problem areas found include management in the form of inaccurate forecasting, capacity management (low machine capacity) and inventory management (insufficient finished goods inventory to meet demand). With the use of the problem analysis tools (Streamline Diagnosis Diagram and Ishikawa Diagram), the root causes for these problems were discovered. Solutions that target and address the root causes were proposed and further evaluated using performance measures and projected cost savings. Recommended solutions include adopting the Multiplicative Seasonal Model forecasting technique, increasing output through overtime and modifying the lot-size values for raw materials in order to drive down inventory costs.